'Otter, come out!': taking away the stone on the southernmost Italian Lutra lutra population. Issue 3 (3rd July 2018) - Gariano, Pasquale; Balestrieri, Alessandro
ABSTRACT: Although Italy is among the European countries with the highest number of threatened species, since the turn of the twenty-first century some flagship species, such as Eurasian otter Lutra lutra and wolf Canis lupus, have started to recover. Since 2003 the otter has been newly recorded on the Sila Massif (S. Italy), where it had been reported to have gone extinct in the 1980s. With the aim of outlining the actual range of this population, in 2014–2017 we monitored otter occurrence on eight major rivers. Spraint surveys were carried out on 18–23 sampling stretches every July. Seven stations (Rivers Savuto and Neto-Lese) showed 75–100% positive surveys, while otters were recorded only once at three of the rivers. Monitoring allowed identifying in the catchments of the Rivers Savuto and Neto, which flow on opposite sides of the Sila Massif, otter core population at the southern edge of its Italian range. We assessed the exceptionality of the recent sightings using a surprise index based on the time distribution of pre-disappearance otter records. Analyses suggest that the otter persisted in the area and went unrecorded during the national survey carried out in 1983–1985, stressing the need for further monitoring at national scale.